Technical report on the 2022 IAB-BiB/FReDA-BAMF-SOEP survey - "Ukrainian refugees in Germany" (Wave 1) - Sabrina Torregroza; Karina Leschny; Michael Ruland; Doris Hess; Reiner Gilberg; Kerstin von der Burg (Deutsches Institut für Wirtschaftsforschung (DIW), 2025)
infas Institute for Applied Social Sciences (infas Institut für angewandte Sozialwissenschaft GmbH) was commissioned to survey refugees from Ukraine by the Socio-Economic Panel (Sozio-ökonomisches Panel, SOEP) at the German Institute for Economic Research (Deutsches Institut für Wirtschaftsforschung, DIW Berlin). The study is a joint project of the Institute for Employment Research (Institut für Arbeitsmarkt und Berufsforschung, IAB), the Federal Institute for Population Research (Bundesinstitut für Bevölkerungsforschung, BiB), the Research Centre of the Federal Institute for Migration and Refugees (Forschungszentrum des Bundesamtes für Migration und Flüchtlinge, BAMF-FZ) and DIW Berlin. The study "IAB-BiB/FReDA-BAMF-SOEP - Ukrainian Refugees in Germany" is financed by the Federal Ministry of the Interior and Community (Bundesministerium des Innern und für Heimat, BMI), the Federal Ministry of Labor and Social Affairs (Bundesministerium für Arbeit und Soziales, BMAS) and the Federal Ministry of Education and Research (Bundesministerium für Bildung und Forschung, BMBF) to find out more about the living conditions of the refugees. To this end, persons between the ages of 18 and 70 who fled Ukraine and came to Germany between 02/24/2022 and 06/08/2022 are surveyed nationwide. This technical report documents the implementation of the first wave in 2022. All survey documents used are documented in the annex. infas Institut für angewandte Sozialwissenschaft GmbH – – Die infas Institut für angewandte Sozialwissenschaft GmbH wurde vom Soziooekonomischen Panel (SOEP) am Deutschen Institut für Wirtschaftsforschung (DIW Berlin) mit der Befragung von Geflüchteten aus der Ukraine beauftragt. Die Studie wird gemeinsam vom Institut für Arbeitsmarkt und Berufsforschung (IAB), dem Bundesinstitut für Bevölkerungsforschung (BiB), und dem Forschungszentrum des Bundesamts für Migration und Flüchtlinge (BAMF-FZ) und DIW Berlin durchgeführt. Die Studie "IAB-BiB/FReDA-BAMF-SOEP - Geflüchtete aus der Ukraine in Deutschland" wird vom Bundesministerium des Innern und für Heimat (BMI), dem Bundesministerium für Arbeit und Soziales (BMAS) und dem Bundesministerium für Bildung und Forschung (BMBF) finanziert, um mehr über die Lebenssituation der Geflüchteten zu erfahren. Dazu werden bundesweit Personen zwischen 18 und 70 Jahren befragt, die zwischen dem 24.02.2022 und dem 08.06.2022 aus der Ukraine nach Deutschland geflüchtet sind. Der vorliegende Methodenbericht dokumentiert die Durchführung der ersten Befragungswelle im Jahr 2022. Alle eingesetzten Erhebungsmaterialien sind im Anhang dokumentiert. infas Institut für angewandte Sozialwissenschaft GmbH
Keywords: 330